Aspek Hukum Pemenuhan Hak Tenaga Kerja terhadap Implementasi Keputusan Pailit Suatu Badan Usaha Sesuai Asas Keadilan - Iron Sarira (Bina Nusantara University, 2011)
The worker is the weaker party in terms of worker-employee relationship system. The problem that often arises in the event of bankruptcy decision issued by the judiciary is the ignorance of labor rights. As we know that termination of employment (layoffs) may be conducted by the employer in accordance with article 165 of Law Number 13 Year 2003 on Manpower, which is when the company is closed due to creditors’ law suit on unpaid credit within a specified time and therefore stating bankruptcy. Employers who are declared bankrupt by a competent judge shall settle all obligations, including in this case, paying workers' compensation regulations. In practice, the curator, the official havint the authority to calculate the company's assets can be invited to cooperate in terms of the repayment obligation, and they rather put the assets of the creditor's rights in front of workers’ rights. The receiver and or parties related to tend to prioritize the interests of the group more than the fulfillment of labor rights as compensation from the bankruptcy decision occurs. Whereas Article 95 Paragraph (4) of Law No. 13 of 2003 has stated that labor rights should come first before completing the receivables of the creditors.